Strategy For Fresh Fruit and Vegetable Suppliers: A Case Study of Botani Fresh Mart - Ghina Kamilia; Dikky Indrawan; Nimmi Zulbainarni (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: West Java's Gross Regional Domestic Product (GRDP) growth rate for the agricultural sector, including the horticulture subsector, exhibited positive values in 2021 and 2022, while several other sectors demonstrated negative growth. However, this trend does not align with the observed conditions at Botani Fresh Mart, namely a decline in sales when the sector’s conditions improved.Purpose: This study aimed to identify the factors influencing fresh vegetable and fruit suppliers and propose recommendations for a suitable business strategy based on this analysis. Design/methodology/approach: This research demonstrates that multiple methodologies can be employed to formulate appropriate strategies for agricultural enterprises, including PESTEL analysis, Porter's Five Forces Model, Structure-Conduct-Performance Concept, Value Chain Analysis, VRIO Framework, IFE and EFE Matrix, IE Matrix, and Analytical Hierarchy Process-SWOT (A'WOT). Findings/result: Internal factors that have a strong influence as strengths are the label inclusion and the ability to plan shipping quotas as weaknesses. The most vital external opportunity factors are (1) government support in opening market access for farmers, (2) increasing vegetable consumption in Indonesia, (3) good horticultural practice regulations, and (4) the number of farmers as potential suppliers. The most vital external threat factor is the conversion of agricultural land. Formulating alternative strategies produced 13 strategies with the priority strategy of increasing the number of partner farmers to ensure product supply.Conclusion: Based on external and internal factors, formulating alternative strategies resulted in 13 strategies. Although the primary priority strategy that can be implemented based on these factors is to increase the number of partner farmers meeting specific criteria, thereby enabling the company to meet market demand, the implementation of other strategies is necessary to enhance the company's performance and support future business growth.Originality/value (State of the art): While the market for fresh produce is growing, Botani Fresh Mart is experiencing a decline in sales. This research aims to develop a customized business strategy for Botani Fresh Mart's unique situation. The proposed approach takes into account both general and industry-specific external factors, as well as internal aspects identified through value chain analysis and the VRIO framework. This comprehensive method ensures that the resulting strategy not only addresses current market and industry trends but also aligns with Botani Fresh Mart's particular strengths and weaknesses. Keywords: A’WOT, business strategy, external environment, fresh produce, internal environment